From artist to artist-researcher *: Adventuring into practice-driven research - Navndrup Black, Laura (Peripeti, 2021)
Presenting a personal account of some of the methodological considerations connected to making the shift from artist to artist researcher, this article asks: how does one create favourable conditions for valid moments of insight to occur in a practice that focuses on participatory choreographic practices involving children and young people? The article unpacks the tangled relationship between ‘practice’ and ‘research,’ and the author proposes the term practice-driven research to suggest an approach where the artistic practice is both the object, the method and the outcome of the research. Drawing parallels to decolonisation practices, the article highlights the importance of shared (re-)naming of central concepts. It is suggested that choreographic strategies that are less concerned with movement language, relying instead on expressive concepts and operating within the field of expanded choreography, may allow the participants to skip the translation of (culturally dependent) movement language and move more readily into a shared, open-ended artistic investigation.Disruption of current prevalent practice within both the social and the artistic field is identified as necessary in order to achieve success in works that span pedagogy, participation and performance (Bishop, 2012), and a practical example of such a disruption strategy based on the KUV project ‘It wont be the same here when it is no longer now’ (2017) is provided.